Paros Island (Cyclades, Aegean Sea) coastal zone: Natural Processes and Dynamics. - Evelpidou, N.; Poulos, S.; Vassilopoulos, A. (Coastal and Marine Geospatial Technologies, 2009)
The present contribution deals with the natural environment of Paros island coastal zone. More than 75% of the coastal zone consists of high and lower cliffs, whilst the relatively flat coastal plains are rare. The island receives a substantial amount of wave energy flux. The largest rocky and of high slopes coastal part is situated at the northeast and northwest part of the island being developed on hard (resistant to weathering processes) metamorphic rocks. Coastal plains (slopes < 2.5%) have been formed on Quaternary clastic formations. Furthermore, sandy and/or pebbly beach zones have been formed by the deposition of terrigenous (mainly) and marine sediments, along relatively sheltered from the wave activity parts of the coastline, i.e. the bays of Drios, Kephalos, Plastiras, Piso Livadi and Alikes. Palaeogeographic reconstruction with respect to sea-level rise within Holocene reveals that Paros island, at 10.000 yr BP, was much larger (some 1.025 km2) combined with the islands of Antiparos, Naxos and several islets, while at 6.000 yr BP was only connected to Antiparos island covering 264.3 km2. Finally, the predicted ca. 0.5 m of sea level rise for the year 2100, due to climatic change, will definitely threaten the socio-economy of the island as all touristic beaches will be deteriorated as well as several  onstructions along its coastline.